Guided Inquiry with Formative Assessment to Reduce Naive Impetus in Learning Newton’s First Law - Jufriadi, Akhmad; Ayu, Hena Dian; Huda, Choirul; Pratama, Ogi Danika (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2025)
This study investigates common misconceptions among students regarding Newton's First Law, specifically their naive impetus, a term used to describe incorrect or incomplete understandings of force. These misconceptions can significantly hinder students' comprehension of key physics concepts. The research explores the various beliefs that contribute to students' naive impetus and examines how their understanding changes before and after the implementation of guided inquiry learning combined with formative assessment. A mixed-methods approach was employed, integrating both quantitative and qualitative data from 30 high school students. The findings revealed four primary misconceptions: the notion of impetus in circular motion, the concept of impetus generated by pulling, the idea of the loss of impetus, and the belief that impetus fades over time. An additional misconception related to the influence of centrifugal force in circular motion was also identified. Following the intervention, students' misconceptions about naive impetus decreased from 76.7% to 33.4%. These results suggest that formative assessments can significantly enhance students' understanding of Newton's laws, particularly in reducing naive impetus and improving academic achievement. The study demonstrates that guided inquiry, combined with formative assessment, is an effective tool for improving students' conceptual understanding. Future research should explore students' misconceptions regarding Newton's Second and Third Laws and examine their relationship with the First Law.